The Speed of Belief: Religion and Science Fiction, an Introduction to the Implicit Religions of Science Fiction - Connor, Kimberly Rae (Implicit religion, 2014)
This article considers the relationship between religion and literature as refracted through the genre of science fiction writing. Connor explores the possibilities for religions created in the hyphen between "science" and fiction. " Religion and science fiction each offers a conception of reality that inclines toward different explanations not just of human behavior but of divine (supernatural) behavior and each suggests differing ideas about how to respond. Using poetry as an additional literary from for understanding the relationship between religion and sciencefiction literature, Connor explores some of the spaces for the invention and expression of religion in its implicit forms.